2014
DOI: 10.1186/s12863-014-0132-5
|View full text |Cite
|
Sign up to set email alerts
|

Heritability for body colour and its genetic association with morphometric traits in Banana shrimp (Fenneropenaeus merguiensis)

Abstract: BackgroundBanana shrimp Fenneropenaeus merguiensis has emerged as an important aquacultured shrimp species in South East Asia and Australia. However, the quantitative genetic basis of economically important traits in this species are currently not available, while for body colour, cooked or uncooked, there are no genetic parameter estimates for any shrimp or indeed any decapod crustacean. In this study, we report for banana shrimp genetic parameters for morphometric traits and, the first time for any shrimp, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 47 publications
6
28
0
Order By: Relevance
“…Astaxanthin accumulation has been shown to correlate with additive genetic effects and is likely heritable, as shown by a single trait mixed model used to estimate heritability of shrimp astaxanthin coloration across a reconstructed pedigree (Nguyen et al, ). Genetic indicator models of sexually selected traits assume that there needs to be sufficient heritability of a trait for it become preferred (Andersson & Iwasa, ).…”
Section: Discussionmentioning
confidence: 99%
“…Astaxanthin accumulation has been shown to correlate with additive genetic effects and is likely heritable, as shown by a single trait mixed model used to estimate heritability of shrimp astaxanthin coloration across a reconstructed pedigree (Nguyen et al, ). Genetic indicator models of sexually selected traits assume that there needs to be sufficient heritability of a trait for it become preferred (Andersson & Iwasa, ).…”
Section: Discussionmentioning
confidence: 99%
“…In shrimp, poor pigmentation was initially described as a disease status (Howell & Matthews 1991), although this was subsequently ameliorated by dietary carotenoid supplementation (Menasveta et al 1993). Recently, pigmentation in banana shrimp has been shown to be heritable (Nguyen et al 2014), indicating there may be a genetic basis to the retention of carotenoid pigments. Crustacean colour variations have also been observed that are unrelated to dietary carotenoids.…”
Section: Carotenoids and Crustacean Colorationmentioning
confidence: 99%
“…The Pacific whiteleg shrimp (Litopenaeus vannamei) is an important crustacean specie that is widely cultured in many countries, especially in Asia and Latin America, where it accounts for about 70% of total crustacean production. Body colour is a trait of commercial importance in crustacean species [1,2]. Many environmental factors largely influence this trait, including light and water temperature [3]; water quality, e.g., the effect of copper [4]; substrate colour [5]; dietary astaxanthin levels [6]; and, rearing tank colour schemes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have shown abundant evidence that shrimp colour can be improved through the manipulation of environmental factors, quantitative genetic basis of this trait while specifically considering objective measurements of body colour is limited in shrimp species [3]. To date, only two studies reported heritability for body colour of banana shrimp based on visual assessment of dark or light colour [1] and Pacific blue shrimp while using the L*a*b* system [9]. The results from these studies suggested that either dark colour of raw or red colour of cooked shrimp could positively respond to genetic selection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation